Excavations in Residential Areas of Tikal--Nonelite Groups Without Shrines : Tikal Report 20B - Haviland, William A. (Book collections on Project MUSE., 2014)
"Excavations in Residential Areas of Tikal-Nonelite Groups Without Shrines is a two-volume presentation of the excavations carried out in and near small residential structures at Tikal, Guatemala, beginning in 1961. These reports show that Tikal was more than a ceremonial center; in addition to its numerous temples, the great Maya city was home to a large population of people. These volumes [Tikal report 20A-B] look at the residential structures themselves as well as domestic artifacts such as burials, ceramic test pits, chultuns."--